The transformative CEO [ impact lessons from industry game changers - Fox, Jeffrey J. , 1945-; Reiss, Robert (New York : McGraw-Hill, 2012)
provides leadership lessons from the world's greatest CEOs. This title helps us learn how CEOs think and act in good times and bad and offers a front-row seat to some of the profitable industry game changers of our time, including AT&T Mobility, Danaher Corporation and more
Keywords: Chief executive officers; Executive ability; Organizational change